Understanding eSports Spectatorship: Players, Fans, Recruits - Carter, Marcus; Gibbs, Martin; Witkowski, Emma (AoIR Selected Papers of Internet Research, 2017)
This research paper reports on interviews with Australian eSports spectators. We identified three primary spectator types – players, fans & recruits – who have substantially different engagements with eSports. Correlating with prior work, Players were drawn to viewing eSports and engaging with third-party content that assisted their pursuit of expertise in the game they played. Fans were more likely to engage with multiple eSports titles and player/team personalities across multiple and integrated digital media outlets, and were characterised by an interest in physically attending tournaments, while Recruits, primarily non-players of eSport titles but ‘gamers’, engaged with eSports stories during notable tournaments and when encountered on social media and content sharing sites like reddit.com. These characteristics of spector types, and types of spectatorship, help us identify numerous insights for the design and development of eSports media.